Detection of cracks in cemented loess of ancient buildings using remote sensing - Lv, Gao; Liu, Naifei; Bao, Liangliang; Yang, Bei; Zhang, Yafei (Frontiers in Materials, 2022)
The base parts of Chinese ancient buildings are prone to deformation, cracks, and other hidden diseases due to long history and other reasons. And rainfall and other seepage water produce great harm to the cracks of soil plinths. Based on the ground-penetrating radar method, the detection of cracks and water erosion defects is important for the protection of ancient buildings. This paper starts from the reflection characteristics of ground-penetrating radar (GPR) waves at different lithological interfaces. The reflection characteristics of GPR incident from brick to air, unsaturated soil, water, metal interfaces are studied by physical experiments and their numerical and physical laws. The model is also applied to the defect detection of the Xi'an Bell tower. The main research results are as follows. The echo amplitude of GPR is positively correlated with the relative permittivity of the bedding layer, and its basic law conforms to the positive logarithmic curve. The hyperbolic opening of water erosion imaging of the base compacted soil is larger, the attenuation effect increases and the signal reflection is obvious. The above results can provide the theoretical basis and technical support for the actual detection of water erosion deterioration of loess in similar projects.